Coping strategies and resilience among patients with hypertension in Ghana - Boima, V.; Yorke, E.; Ganu, V.; Gyaban-Mensah, A.; Ekem-Ferguson, G.; Kretchy, I.A.; Mate-Kole, C.C. (Frontiers in Psychology, 2023)
Background: Hypertension is associated with high morbidity and mortality and this has been linked to poor treatment and control rates. To optimize drug treatment, patient-centered strategies such as coping, resilience, and adherence to medication may improve control rates and decrease the morbidity and mortality associated with hypertension. This study, therefore, assessed coping skills and resilience among patients with hypertension in Ghana. Methods: A cross-sectional study was conducted at Korle Bu Teaching Hospital. 224 consented patients with a diagnosis of hypertension were consecutively selected from the outpatient clinic. Questionnaires comprising socio-demographic characteristics, clinical parameters, Adult Resilience Measure, and the Africultural Coping Systems Inventory were administered. Data were analyzed using Stata version 16.1 and significance level was set at p-value of ≤ 0.05. Results: The mean age of participants was 62.03 ± 11.40 years and the majority were female (63%). The overall coping strategy mean score was 43.13 ± 13.57. For resilience, median relational and personal resilience (PR) scores were 32 (IQR-7) and 39 (IQR-9), respectively. Increased systolic BP significantly increases the overall coping strategy score. Collective coping strategy and systolic BP significantly increased coping scores (95%CI = 0.05–3.69 vs. 95%CI = 0.58–5.31). Overall coping strategy significantly increased personal and relational resilience (RR) domain scores by 0.004 (95%CI = 0.002–0.01) and 0.005 (95%CI = 0.003–0.006) units, respectively. This study demonstrated that Cognitive and emotional debriefing coping strategy was mostly used by patients with hypertension. Conclusion: Coping strategies had a positive and significant correlation with personal and RR, specifically collective and cognitive debriefing had a significant positive association with resilience among study participants. There is a need to actively put in measures that can improve the coping strategies and resilience among patients with hypertension to adjust to the long-term nature of the illness and treatment as this will promote better treatment outcomes.
Research Article
Keywords: coping strategies; resilience; hypertension; cognitive debriefing